APLIKASI ALGORITMA DYNAMIC PROBABILISTIC INVENTORY PADA PROSES PENGENDALIAN PERSEDIAAN BAHAN BANGUNAN - Ngarap Im Malik; Evelin Widyawati; Rudi Tjiptadi (Jurusan Teknik Informatika, 2010)
In a building construction project, optimizing of inventory control plays an important rule to guarantee continuity and fluency of the project. It is needed to choose a suitable model to control it, so the total cost of inventory can be minimized. This paper discusses a dynamic probabilistic inventory model. With this model the accurate average ordering can be known, as well also optimal ordering quantity, the minimum amount of stock inventory, and reordering time, so the total inventory cost can be minimized. Discuss here only the critical building materials, namely materials type A, because this type of materials needs big amount of company’s budget, so when it is well controlled, the budget of the company can be well saved / minimized.